Conceptions of functions among first degree and diploma students / Siti Aishah Sheikh Abdullah - Sheikh Abdullah, Siti Aishah (Institute of Research, Development and Commercialization (IRDC), 2007)
The concept of functions is one of the most important topics in mathematics learning. However many studies have indicated various difficulties students exhibited in learning the concept of functions. Tall & Vinner used the term concept images to describe how students think about concepts. A person S concept image can differ greatly from the formal mathematical definitions of the concept. This study explores an aspect of understanding the concept of functions related to this theme. One hundred and ninety university students from two different universities and with a different academic background participated in the study. The first group of students were diploma students in their second semester of engineering programme. The second group were first year students enroll in science based degree in another higher institutions. Data were gathered from questionnaires which asked students to identify functions in graphic and algebraic forms. They were also requested to give reasons for their choices. A large number of students indicated a strong tendency to observe function only as a formula between x and y. Their justification for rejecting or accepting representations of functions showed a rather rigid and limited understanding of the concept. Many were unable to give clear reasoning explaining their choices according to the formal definition from their previous learning.